THE EFFECTS OF HUMAN CAPITAL DEVELOPMENT, AND WORK DISCIPLINE, AGAINST EMLOYEE’S PERFORMANCE AT PARK HOTEL JAKARTA - Aditia Rahman; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2016)
Purpose- . Aiming to measure the human capital development and work discipline against employee’s performance at Park Hotel, Jakarta Design/methology/approach- A questionaire survey to employees Park Hotel, Jakarta.The sample were 100, selected by purposive, within a single organization supported by interviews. Data analyzed by multiple regression using SPSS version 20 Findings- Overall tests done, it is concluded that work discipline has a very strong effect against the employee’s performance. This is also still positively effected, the human development program and work discipline have effected Employee’s performance, simultaneously. Research limitations- The limitation of this research lies on its scope of object, and the limited variables involved. It I s then suggested for the next research that other variable such as compensation, and other exogen variable can be deployed too. Practical implications-The manager of human resource shall maintain and develop the potential of employees by providing a combination of human resource development. There are many choice to choose from training, education, rotation, vestibule, vide show, including self esteem program. Additionally a main area to evaluate the existing compensation, as it has a bigger effect on employee’s performance. The Originality-This is done exclusively for the Park Hotel as a single company that may applicable therein, and therefore it easier to be improved.